Polyamine-mediated turnover of ornithine decarboxylase in Chinese-hamster ovary cells. - Glass, J R (1986)
We have used Chinese-hamster ovary (CHO) cells maintained in a chemically defined medium to study the regulation of ornithine decarboxylase (ODC) by polyamines. Cells maintained in the defined medium had no detectable putrescine, and approx. 1-3 units of ODC activity/10(6) cells, where 1 unit corresponds to 1 nmol of substrate decarboxylated in 30 min. The defined medium is ornithine-deficient, thus limiting the exogenous substrate for ODC, and subsequently decreasing intracellular polyamine accumulation. Restoration of intracellular putrescine and increased formation of spermidine by addition of exogenous ornithine or putrescine led to a marked decrease in ODC activity, which was paralleled by a decrease in a alpha-DL-difluoromethyl[3,4-3H]ornithine (DFMO)-binding protein of Mr approx. 53,000, which is precipitable with anti-ODC antibody. Calculation of DFMO binding per unit of activity showed no change in the specific activity of the enzyme. We identified [35S]methionine-labelled peptides corresponding to ODC by immunoprecipitation of radiolabeled whole cell proteins. Only one protein was precipitated, of Mr approx. 53 000, which co-migrated with the DFMO-binding protein. Immunoprecipitation of radiolabelled proteins from cells incubated in the presence of exogenous ornithine indicated that the observed activity decrease was not due to an inhibition of ODC protein synthesis. Analysis of immunoprecipitable ODC protein from cells that had been pulse-labelled with [35S]methionine, and then treated for 5 h with 100 microM-ornithine, -putrescine or -spermidine, revealed a distinct disappearance of labelled ODC protein after restoration of intracellular polyamine pools. No detectable turnover of ODC was observed in the absence of exogenous polyamine treatment. These data support the hypothesis that ODC protein, and subsequent activity, is regulated by intracellular polyamine content through mechanisms that influence turnover of the enzyme.